Online learning adoption in a developing countries : a case of the Indonesian Open University - Aditiawarman, Umar (IIUM Press, 2011)
As many academic institutions adopt web-based learning or online learning to deliver variety of courses, the effectiveness and efficiency of these new technologies are still doubtful. By adopting TAM as research model, this study tends to investigate factors influencing online learning adoption in Universitas Terbuka (UT), Indonesia.